Relationship of Neutrophil-to-Lymphocyte and Platelet-to-Lymphocyte Ratio With Visual Acuity After Surgical Repair of Open Globe Injury - Mohamed-Noriega, Karim; Treviño-Herrera, Alan B.; Mohamed-Noriega, Jibran; Velasco-Sepúlveda, Braulio H.; Martínez-Pacheco, Víctor A.; Guevara-Villarreal, Dante A.; Rodríguez-Medellín, Delia L.; Sepúlveda-Salinas, Anna G.; Villarreal-Méndez, Gerardo; González-Cortés, Jesús H.; Elizondo-Omaña, Rodrigo E.; Guzmán-López, Santos; et al. (Frontiers in Medicine, 2021)
Purpose: To assess the relationship and prognostic value of the neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) with poor final best-corrected visual acuity (BCVA) after surgical repair of open globe injuries (OGI) in adults. Design: Retrospective analysis of data from an ongoing prospective cohort of consecutive patients. Methods: In a tertiary university hospital, 197 eyes of 197 patients were included between 2013-2017. NLR and PLR were obtained from preoperative blood tests to analyze its relationship with poor final BCVA. Results: Severe visual impairment (SVI) was defined as ≤ 20/200, and was observed in 96 (48.7%) patients after surgical repair of OGI. SVI patients had higher NLR (7.4±6.6 vs 4.0±3.2, p<0.001), and PLR (167±92 vs 139±64; p=0.021) than non-SVI. NLR3.47 and PLR112.2 were the best cut-off values for SVI, were univariate risk factors for SVI, and had sensitivity: 69.0, 71.4, and specificity: 63.6, 44.8, respectively. In multivariate analysis, only OTS, athalamia, and hyphema remained as risk factors. NLR had significant correlation with ocular trauma score (OTS) (r=-0.389, p<0.001) and final BCVA (r=0.345, p<0.001). Limitations: Simultaneous trauma in other parts of the body that could influence the laboratory findings. Conclusion: Patients with SVI after a repaired OGI had increased pre-operative NLR and PLR levels. High NLR and PLR are risk factors for SVI in univariate analysis. It is confirmed that low OTS is a risk factor for SVI. High NLR and PLR could be used as a prognostic tool to identify patients at higher risk for SVI after repair of OGI.